Antifungal Activity of Polyscias scutellaria Fosberg Leaves Against Candida albicans - Marcha Putri, Nada; Regita Putri, Jasmine; Elya, Berna; Adawiyah, Robiatul (UI Scholars Hub, 2020)
Polyscias scutellaria Fosberg is one of the indigenous plants from Indonesia that widely used as folk medicines for several illnesses. The leaves of P. scutellaria were previously studied as an antimicrobial agent. Nonetheless, this theory of antifungal activity has never been scientifically verified. This study aimed to evaluate the antifungal activity of P. scutellaria against Candida albicans. The leaves of P. scutellaria were macerated using an ethanol solvent. Then, the extract was evaporated and dissolved by 1% DMSO into different concentrations (100 μg/mL, 200 μg/mL, 400 μg/mL, 800 μg/mL, 1600 μg/mL, 3200 μg/mL, and 6400 μg/mL). Fluconazole, as a common antifungal treatment, was used as the positive control. The antifungal activity of P. sculletaria against Candida albicans was tested using well dilution and diffusion disc methods. Ethanol extract of P. scutellaria leaves showed antifungal activities against Candida albicans. It showed the minimum inhibitory concentration of above 6400 μg/mL and formed the inhibitory zone against Candida albicans. As a conclusion, ethanol extract of P. scutellaria has the potential to be used as an antifungal agent against Candida albicans.